2020
DOI: 10.1101/2020.07.21.205765
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nitrapyrin has far reaching effects on the soil microbial community structure, composition, diversity and functions

Abstract: Nitrapyrin is one of the most common nitrification inhibitors that are used to retain N in the ammonia form in soil to improve crop yields and quality. Whereas the inhibitory effect of nitrapyrin is supposedly specific to ammonia oxidizers, in view of the keystone role of this group in soils, nitrapyrin could have far-reaching impacts. Here, we tested the hypothesis that nitrapyrin leads to large shifts in soil microbial community structure, composition, diversity and functions, beyond its effect on ammonia-ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 79 publications
1
1
0
Order By: Relevance
“…Previous studies ( 43 , 47 ) suggested a selective effect of DCD on the diversity of AOB, while AOA were not affected, in line with our findings. Recently Schmidt et al ( 23 ) showed that NP, when applied at rates similar to our high dose rate, induced a significant shift on the AOA soil community, in accord with our results. Our study provides first evidence for the effects of NP and QI on the diversity of AOB and AOA, indicating a greater impact of both compounds on AOB compared to AOA, even in soils numerically and functionally dominated by AOA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies ( 43 , 47 ) suggested a selective effect of DCD on the diversity of AOB, while AOA were not affected, in line with our findings. Recently Schmidt et al ( 23 ) showed that NP, when applied at rates similar to our high dose rate, induced a significant shift on the AOA soil community, in accord with our results. Our study provides first evidence for the effects of NP and QI on the diversity of AOB and AOA, indicating a greater impact of both compounds on AOB compared to AOA, even in soils numerically and functionally dominated by AOA.…”
Section: Discussionsupporting
confidence: 93%
“…The studies available have explored the effects of DCD- (or DMPP-) fortified fertilizers on the abundance of bacteria or fungi or on microbial community structure determined by low-resolution methods (e.g., PLFAs and DGGE), with contradictory results ( 21 , 22 ). On the other hand, the potential effects of NP on nontarget soil microorganisms are less studied, with recent reports suggesting possible effects on the overall soil microbial community within and beyond N cycling ( 23 , 24 ). Careful evaluation of the off-target effects of NIs on the soil microbiota is essential to define potential risks associated with their use in agricultural settings that might compromise soil ecosystem diversity and functioning, beyond nitrification and N cycling.…”
Section: Introductionmentioning
confidence: 99%